THE CONCEPT OF HABITUS - TOWARDS A COMPREHENSIVE SOCIOLOGICAL THEORY OF CAREER CHOICE - Lucian MOCREI-REBREAN (Association of Social and Educational Innovation, 2021)
When searching for a sociological perspective on career choice-related problems, the issue of social rationality comes into focus. The labor markets provide structural opportunities, but are jobs simply allocated at a macro-social level, or individually chosen? By looking for an explanation strictly within a macro-social frame of reference, we came to a conclusion that may seem biased: social structure determines professional choices. But Structuralism fails to account for individual free will or social group influence. Group beliefs and values are always confronted with real labor market opportunities. We need theoretical models of career choice that can accommodate both the macro and micro social levels of understanding. We take Pierre Bourdieu's theory of praxis as a middle-range comprehensive theory rather than an all-encompassing explanation because it is not based on a priori statements but on empirical data. The rationality of social actors cannot be understood without comprehending their shared aspirations, motivations, constraints, beliefs and values, all of which are linked to their pragmatic rationality. This notion efficiently describes the permanent negotiations between the micro and macro levels of social existence, leading us to the concept of habitus. The individual physical, practical, emotional and cognitive dispositions that constitute the habitus, are continuously mediated by social structures. Negotiated within specific social fields, career decisions emerge as an interaction between the two levels.